Biodegradation of methylmercury by bacteria of Empedobacter brevis in leachate - Meli Anggraini; Muhammad Said; Suheyanto Suheryanto (Indonesian Journal of Environmental Management and Sustainability, 2018)
Leachate treatment containing methylmercury (CH3Hg+) can be done by using biodegradation method. Bacteria used in methylmercury biodegradation of the bacteria Empedobacter brevis. This study aims to examine the ability of bacteria in degrading methylmercury in leachate and determine the value of ?max and Ks. The degradation process is done with variation of inoculum concentration and incubation time aerobically. The parameters analyzed were the decrease of methylmercury content in the biodegradation process. The results showed that biodegradation of methylmercury by the bacterium Empedobacter brevis at 15% inoculum concentration was the highest decrease efficiency of 81%. The values of ?max and Ks in the bacterium Empedobacter brevis were 0.994 per hour with a substrate concentration of 1.588 mg /l.